The ray projection method: A numerical approach for determining ideal camera placement - Manal, K. T.; Gardinier, J. (Journal of Applied Biomechanics, 2007)
Data piloting is important to ensure accurate marker coordinate data and to minimize camera dropout. Camera dropout results when a camera fails to image a marker, which often occurs when markers merge or become occluded. In this article, we present the conceptual framework for a numerical method of determining where video cameras, if placed, would have an occluded or a merged view of the tracking markers. Experimental data are presented to demonstrate the efficacy of the method as a tool to complement existing data piloting procedures.